Retraction notice to influence of nucleotomy on the load sharing in the spinal facet joint under the loading scenarios of different human postures. (April 2022) - Lu, Yongtao; Cheng, LiangLiang; Zhu, Hanxing
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editor-in-Chief. The authors have failed to cite or to acknowledge prior work appropriately. (The author of that prior work preferred for its details not to be included in this notice.) One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited.